A comparative analysis of start-up access to external funding in the EU and Western Balkans - Kruja, Iris; Irimia-Diéguez, Ana I. (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to compare the access to external finance of start-ups between the Western Balkans and European Union (EU) countries, exploring differences and commonalities in their entrepreneurial finance ecosystems. A composite Access to Finance Index was developed, integrating five key indicators: Fitch sovereign credit ratings, private sector credit-to-GDP ratio, venture capital investment volume, stock market capitalization relative to GDP, and the investor protection index. These indicators provide a multidimensional assessment of financial system maturity and institutional quality relevant to start-up development. The study shows that there are significant disparities between the EU and the Western Balkans. EU countries show higher institutional and financial maturity, including better credit ratings, deeper venture capital markets, and stronger investor protections. Western Balkan countries, by contrast, face constraints in all measured areas, though some exhibit emerging potential. The EU provides a more conducive environment for start-up financing, while the Western Balkans require substantial institutional and financial reforms to bridge the gap. The study offers policymakers and stakeholders a structured framework for diagnosing financial barriers and prioritizing reforms. Recommendations include strengthening legal protections, fostering venture capital ecosystems, and leveraging cross-regional cooperation to support inclusive start-up growth.